THE CONCEPT OF SELF EFFICACY AND RELATED ACADEMIC STUDIES - ARSLAN, Serap (Atlas Journal, 2021)
Throughout their lifetime, human begins struggle to survive, cope with difficulties, protect their mental health and adapt to new situations. The self efficacy level of the person is important in dealing with such situations. The concept of self efficacy is the belief that an individual develops in order to be self sufficient and to do a job. How individuals perceive their self efficacy beliefs may be related to mental problems, family and friendship relations, academic and work performances. For this reason, individuals’ perception of their self efficacy levels correctly and the development of their beliefs about this explain the importance of the research. The aim of the study is to explain the concept of self efficacy and to examine which areas the concept of self efficacy is associated with and which areas it is related to. In this context, academic studies on the concept of self efficacy in the literature of 2000 year and after were discussed and conveyed in a semantic integrity. In addition, the scales developed within the scope of self efficacy were introduced and the analyzes made inferred about the data obtained from these scales were mentioned. In the conclusion part of the study, evaluation was made regarding the development of self efficacy and the working areas of self efficacy and recommendations were made.